GE_GERICHTE P/27092/2023 vom 14. Juli 2025 - GE Cour de justice (2025)
VIDÉOSURVEILLANCE;CIRCULATION ROUTIÈRE(DROIT DE LA CIRCULATION ROUTIÈRE);PRÉSOMPTION D'INNOCENCE | LCR.90; LVA.14.al1; LCR.93.al2.letb; CPP.141; LCR.57c; LCR.57d; CPP.10.al2; CPP.10.al3